Analisis Faktor Faktor yang Mempengaruhi Kredit Macet pada Perseroan Terbatas Dharma Pejuang Empat lima di Kabupaten Lima Puluh Kota - Hariman Syaleh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This research aims to determine the influence of education, gender, occupation, age, status, number of dependents and income on Dharma PT.BPR Empatlima fighters in District Fifty State the period 2011 to 2015. The research object In this research are datas of non perfoming loan in PT.BPR Dharma Pejuang Empatlima year 2011 to 2015. This research was analyzed using multiple linear regression through T test and F test and coefficient of determination (R2). Based on the result, it is known that education (X1), job (X3), age (X4), number of family dependent (X6) and income (X7) have significant effect on non performing loan in PT.BPR Dharma Pejuang Empatlima. Gender (X2) and status (X5) have no significant effect on the occurrence of non performing loans at PT.BPR Dharma Pejuang Empatlima. The result of F statistic shown the education, sex, occupation, age, status, number of dependents and income are given simultaneously significant effect on the occurrence of non performing loan in PT.BPR Dharma Pejuang Empatlima. Keywords : Education, Gender, Job, Age, Number of family dependent Income and non performing loan.